Puasa Dan Kesehatan Mental (Psikologi Konseling) - Wildan Halid (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2023)
Fasting is a personal worship which is legally called worship which is fardu 'ain in nature, worship whose value is directly measured by Allah SWT, apart from fasting being obligatory in this case fasting in the month of Ramadan, there are also fasts which are of a sunnah nature, regardless from the orders and suggestions, the author examines from a scientific point of view as an academic, the author examines the impact of fasting in terms of physical and psychological health. Fasting is a ritual worship that is very influential on mental and physical health, this is proven by various medical studies. The impact on all organs of the body and mind even goes beyond the benefits of meditation which are encouraged by meditation activists because the spiritual energy generated from fasting is very broad. This is due to the presence of metaphysical energy that can be proven scientifically. What's more interesting is that fasting is used to cure serious illnesses such as stroke and other physical ailments, as well as other mental illnesses, such as schizophrenia and bipolar. Because when fasting is used as a healing medicine, it is not just a holiday from eating and drinking, but it involves a power that we cannot reach, namely a direct connection with the Almighty.